AN ANALYSIS OF CODE SWITCHING IN INDONESIAN MOVIE “BRIDEZILLA” - Hendryani, Kadek Dessy Dwi; Paramartha, A.A. Gede Yudha; Juniarta, Putu Adi Krisna (Universitas Pendidikan Ganesha, 2021)
This study aimed to analyzethe types and functions of code switching used by the actors and actress in Indonesian movie entitled “Bridezilla”. This study used descriptive qualitative method. In collecting the data, this study used document analysis method with checklist analysis form and taking a note as the instruments used. There 5 were steps done in order tocollect the data, such as watching movie, giving mark in the checklist analysis form, taking a note, giving explanation and conclusion based on the results of analysis. It was found that in “Bridezilia” movie consisted ofcode switching in 35 dialogs, there were three types of code switching, such as Tag-Switching13 dialogs, Inter-Sentential 10 dialogs and Intra-Sentential Switching in 12 dialogs. Meanwhile, there were 2 functions of code switching existed in the movie. It can be concluded that the existence of code switching in Indonesian movie indicating that the other language has big impact toward the first language.